A-280 Residual Cognitive Weaknesses in a Case of Treated Seronegative Autoimmune Encephalitis. (17th August 2022) - Ross, Daliah; Yaffe, Beril
Abstract: Objective: Autoimmune encephalitis (AE) refers to a group of syndromes involving brain inflammation due to autoimmune activity and is associated with acute cognitive impairment. While several identified AE-associated antibodies (e.g., NMDAR) can be detected in cerebrospinal fluid and blood serum, many patients who respond well to treatment do not have the AE-associated antibodies. This causes challenges in diagnosis and treatment and has led to limited literature prognosticating cognitive outcomes following treatment in cases of suspected seronegative AE. We describe a case of seronegative AE in a patient with lingering cognitive symptoms after resolution of acute symptoms post-immunotherapy. Method: Patient is a 25-year-old female with a history of ulcerative proctitis who presented with suspected AE in the context of seizure, fever, balance difficulties, and personality changes. While antibodies were not detected, she was diagnosed with AE based on presentation, inflammatory markers, and neuroimaging and was treated with steroids, intravenous immunoglobulin, and plasma exchange. Patient presented for neuropsychological assessment 10 months later with lingering cognitive complaints. Results: Neuropsychological testing posttreatment revealed weaknesses/variability in attention, working memory, processing speed, and aspects of executive functioning including executive aspects of memory. Language, visuospatial functions, and retentive memory were preserved. Conclusion: This case suggested continued frontal-subcortical dysfunction likely related to residual effects of AE. Side effects of medications may have also contributed to her cognitive weaknesses. This case highlights the need for more research examining cognitive prognosis and expected timelines post seronegative AE treatment, given limited existing research. This is an important consideration for interpretations and recommendations from our neuropsychological evaluations.